Kesulitan Penggunaan Present Perfect dalam Pembelajaran Bahasa Inggris - Tawarniate, Reduk; Sya, Mega Febriani; Dianti, Alya Meysa (Karimah Tauhid, 2024)
Present Perfect is one of the most commonly used verb tenses in English to indicate an action that occurred in the past and continues to the present. However, there are still many people who do not understand the use of Present Perfect. The purpose of this writing is to explain how to use Present Perfect in English sentences. This research uses a descriptive method with a literature review taken from previous sources. As a result, we can understand better and can create Present Perfect sentences which are used to express past actions that are still continuing into the present. Keywords: Present Perfect Kata kerja Present Perfect adalah salah satu bentuk kata kerja yang paling umum digunakan dalam Bahasa Inggris untuk menunjukkan suatu tindakan yang terjadi di masa lalu dan terus berlangsung hingga saat ini. Namun masih banyak orang yang belum memahami kegunaan Present Perfect. Tujuan penulisan ini adalah untuk menjelaskan bagaimana penggunaan Present Perfect dalam kalimat Bahasa Inggris. Penelitian ini menggunakan metode deskriptif dengan kajian literatur yang diambil dari sumber-sumber terdahulu. Hasilnya, kita bisa lebih memahami dan bisa membuat kalimat Present Perfect yang digunakan untuk mengungkapkan tindakan masa lalu yang masih berlanjut hingga saat ini. Kata Kunci: Present Perfect